ANALISIS KUALITAS SUMBER DAYA MANUSIA DALAM MEMBERIKAN PELAYANAN ELEKTRONIK DI APLIKASI PLN MOBILE - Katamsi, Khusaeri; Setiyarti, Tettie (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The objective of this article is to examine the factors influencing the introduction of innovation in public services via the PLN Mobile app at PT. PLN (Persero), focusing on the constraint of the app's availability solely on Playstore for Android devices. Additionally, the article seeks to propose suggestions for enhancing the accessibility and quality of public services through the PLN Mobile app. The research methodology employed in this article is qualitative, involving a case study of PT. PLN (Persero) and the analysis of pertinent secondary data. Data were gathered through literature review, relevant documentation, and interviews. Findings reveal that the limitation of the app being exclusively on Playstore for Android devices adversely affects the accessibility and efficiency of public services via PLN Mobile. Nonetheless, there exists potential for enhancing accessibility and service quality through specific measures, such as expanding the app to other platforms and educating customers.